Control of cyclic oligoadenylate synthesis in a type III CRISPR system - Rouillon, Christophe; Athukoralage, Januka S; Graham, Shirley; Grüschow, Sabine; White, Malcolm F (eLife, 2018)
The CRISPR system for prokaryotic adaptive immunity provides RNA-mediated protection from viruses and mobile genetic elements. When viral RNA transcripts are detected, type III systems adopt an activated state that licenses DNA interference and synthesis of cyclic oligoadenylate (cOA). cOA activates nucleases and transcription factors that orchestrate the antiviral response. We demonstrate that cOA synthesis is subject to tight temporal control, commencing on target RNA binding, and is deactivated rapidly as target RNA is cleaved and dissociates. Mismatches in the target RNA are well tolerated and still activate the cyclase domain, except when located close to the 3’ end of the target. Phosphorothioate modification reduces target RNA cleavage and stimulates cOA production. The ‘RNA shredding’ activity originally ascribed to type III systems may thus be a reflection of an exquisite mechanism for control of the Cas10 subunit, rather than a direct antiviral defence. The gene editing tool often known simply as CRISPR has become well known in recent years. Its potential applications are wide ranging, including uses in research, healthcare and agriculture. Yet, the CRISPR system originated in microbes where it helps to protect them from viral infections. Viruses infect by inserting their own genes into a host cell, and – almost like a pair of scissors – the CRISPR system can cut up the virus’s DNA to stop infections. CRISPR experts know the popular form of CRISPR as type II, but there are others. Type III CRISPR is less useful as a genetic tool but does also protect microbes from viruses. In addition to targeting DNA, type III CRISPR targets the related RNA molecules from viruses. When it encounters RNA from a virus, the type III CRISPR produces a small molecule called cyclic oligoadenylate (or cOA for short). The cOA molecule activates enzymes known as non-specific ribonucleases, which can destroy all the RNA in the cell. This defence is a less subtle than that provided type II CRISPR and can also damage the cell by destroying other RNA molecules that the microbes use to survive. As such, proper regulation is essential to prevent the type III system from unnecessarily killing the infected cell. Rouillon et al. studied the control of the type III CRISPR system from the heat-loving microbe Sulfolobus solfataricus, which is found in volcanic springs. This species has been a model for studies of the CRISPR system for many years, in part because its proteins are very stable which makes them easier to work with in the laboratory. The results show that the type III CRISPR makes cOA by combining four molecules of adenosine triphosphate (ATP) into a ring. CRISPR responds immediately to viral RNA in the cell. It also detaches from the RNA as soon as it starts to be destroyed. Rapid activation and silencing of the production cOA ensures that the CRISPR system is tightly controlled. These findings reveal that cOA production is tightly linked to the abundance of viral RNA, ensuring a proportional and timely response to infection. Using cOA amplifies the cell's response because it allows a single RNA molecule to activate a larger change. Type III CRISPR systems are widespread in nature, and a better understanding of them could improve the yield of products, like yoghurt, that depend on healthy bacteria; currently viruses cause a lot of economic damage in this industry. Further research in this area could also lead to new antibiotics that over-activate type III CRISPR to destroy bacterial cells.